Development of Wave Energy Conversion Technologies in Sumatera Utara - Rakhmad Arief Siregar; Muhammad Yusuf Rahmansyah Siahaan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2026)
The increasing energy demand and the serious impact of fossil fuel use on the energy crisis and climate change encourage the development of more sustainable renewable energy sources. This study aims to design a wave conversion device as an alternative energy source for the future. A quantitative approach was used through the distribution of structured questionnaires to 35 respondents, with 29 data points declared valid for analysis. The study focused on user attitudes, knowledge, and behavior towards the device design. Preference data were processed using morphology tables and decision matrices to obtain the most appropriate design. The results showed that respondents tended to choose a pendulum operating system, a horizontal device position, and an aluminum frame, with an expected price below IDR 10 million and preventive maintenance every six months. Based on the evaluation, Concept A was selected as the best design because it was considered technically superior, easy to maintain, cost-effective, and suitable for field conditions. This design was then visualized using CAD software to support the prototyping process. This study shows that the design of a marine energy device that considers user needs and preferences can produce a more realistic, affordable solution and has the potential to strengthen the implementation of marine energy in the transition agenda towards sustainable clean energy. The resulting design offers the development of marine energy technology that is applicable and relevant to the needs of coastal communities.